The Role of Customer Participation and Brand Engagement in Enhancing Brand Loyalty in Digital Environments - Satija, Arushi (Digital Repository of Theses - SSBM Geneva, 2025)
In the fast-evolving scenario of digital marketing, insight into consumer-brand interaction dynamics has become pivotal for sustaining competitive advantage. This study examines customer participation, brand engagement, and brand loyalty relationships of digitally active consumers in the Delhi NCR region. As digital platforms grow to become an integral portion of brand communication/customer experience, an examination of how consumer behaviors in these spaces translate into long-term brand relationships becomes essential. The study adopts a quantitative methodology rooted in deductive reasoning and a descriptive-correlational approach in testing hypothesized relationships among the proposed key variables. Data collection was done through a structured online survey conducted with consumers in the past 6 months, in which communication with the brands was done in the digital settings, including social media, e-commerce sites, and online communities. With the purposive and snowball sampling procedures, approximately 300–400 respondents were targeted in order to meet the inclusion criteria established as pertinent to the objective of this study. The final data set was of 391 respondents that was used to conduct the analysis. Descriptive statistics were used on the primary data to describe the characteristics and behavioral patterns of respondents, while inferential methods, including correlation and regressions, were used to measure the strength and direction of relationships among the constructs. The study found significant positive correlations between customer participation and brand engagement, and between brand engagement and brand loyalty. Regression analysis also confirms that brand engagement and customer participation have a significant impact on brand loyalty. The contributions of this study are theoretical and practical, having provided empirical evidence on the need to involve customers in digital brand activities to increase engagement and loyalty over the longer haul. This paper offers marketers and brand managers useful insights as they seek to engage digitally. The research furthers contextual relevance within the growing body of literature on digital consumer behavior in emerging economies with the lens of a major urban digital hub, Delhi NCR.